Online or offline supervision? Postgraduate supervisors state their position at University of South Africa - Gumbo, M.T. (South African Journal of Higher Education, 2019)
The demands of postgraduate supervision are huge for supervisors. These demands can however be lessened by taking advantage of the online operated information and communication technology (ICT). Supervising online provides important tools and/or applications which are the 21st century era enablers of supervision especially in an open and distance learning (ODL) institution such as University of South Africa (UNISA). The supervisor-student working relationship, however, presents a human aspect that should take precedence over technology and thus guide how technology can be used in supervision. It is in this light that this reported study inquired into the supervisors’ knowledge of the technological tools and their stance in the use of (online) technology in their supervision given the human aspect. UNISA’s hundred-and-twenty-nine supervisors who are attached to College of Education (CEDU) were investigated in this study with respect to their supervision characteristics and exposure to technology and level of knowledge of the technological tools. That was followed up by face-to-face interviews with seven supervisors to determine their stance about the use of technology given the human aspect of students. The findings showed that the supervisors are knowledgeable in terms of the tools or applications such as MS Word, myUnisa and Discussion Forum. Furthermore, the findings indicated that there is a need for the training of other supervisors with respect to the use of certain online applications and/or tools. The most important finding is that supervisors value the human aspect such that – though supervisors are positive about the role of technology in supervision, the human aspect should enjoy precedence in their supervision of students.